A Portal for Cataloging Worked Examples Extracted from Open Source Software - Tonhão, Simone de França; Colanzi, Thelma Elita; Steinmacher, Igor (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Finding real examples that follow the evolution of Software Engineering is not an easy task for instructors in the field. Open Source Software (OSS) projects have been an alternative to support education in Software Engineering, as they allow contact with real development projects and environments. However, the adoption of these projects in the classroom presents some obstacles, such as choosing the appropriate project, and the time and effort needed to prepare the classes and get used to the open source environment. In order to reduce the difficulties faced by instructors, we are working on developing a portal to catalog worked examples extracted from OSS projects to assist instructors. In this paper, we present the first steps towards creating this catalog, which is creating a pattern for guiding the structuring the worked examples. We are applying the Design Science Research paradigm. The activities reported in this paper regards the first Design Cycle, and were divided into three stages related to the elaboration and evaluation of the pattern for cataloging the worked examples. In these stages, we carried out focus groups and interviews with Software Engineering instructors, including the instantiation of the pattern to catalog actual worked examples. After each stage, we had a new and improved version of the pattern for cataloging the worked examples. Such pattern served as a basis to create the first version of the worked examples portal, which will be evaluated in the next stages of the research.